Analysis of Research Data: using EViews - Avwokeni, Arthor J. (Lagos, Nigeria, 2021)
This book is a training manual on the analysis of data secured within the research setting. It can be used as a reference manual when planning and designing a research project.
Includes bibliography, index
osc 20/02/2024
Loans
Keywords: Research methods